Cinnamomum zeylanicum extracts reduce lipid oxidation in broadband anchovy (Anchoviella lepidentostole) minced fish - Simbine, Emelda Orlando; Rodrigues, Larissa Da Cunha; Burbarelli, Maria Fernanda De Castro; Fávaro-trindade, Carmen Sílvia; Viegas, Elisabete Maria Macedo; Enke, Dariane Beatriz Schoffen [UNESP]; Lapa-guimarães, Judite (Sociedade Brasileira de Ciência e Tecnologia de Alimentos, 2021)
Minced fish (MF) is an interesting material for development of novel fish products; however, the mechanical deboning process interferes with MF quality, by increasing the lipid oxidation. This study reports the effect of Ceylon cinnamon (Cinnamomum zeylanicum) hydro-ethanolic bark extracts as natural antioxidants on both washed and unwashed MF of broadband anchovy during six months of storage at -18 °C. Spray-dried cinnamon extract (DC) and spray-dried cinnamon extract using maltodextrin 10DE (DCM) as a carrier were evaluated in relation to antioxidant activity in vitro. DC and sodium erythobarte were added to both washed and unwashed MF at 0.25% (w:w), whilst DCM was added at 1.055% (w:w). The DC extract presented higher antioxidant activity in vitro compared to DCM extract. The addition of cinnamon extracts reduced the lipid oxidation in washed and unwashed MF compared with the controls. C. zeylanicum extracts can be used to prevent lipid oxidation in MF during the frozen storage and are alternatives for food industries that seek to meet the demand of consumers increasingly concerned with the consumption of healthy foods.
Keywords: antioxidant activity; natural extracts; fish products